(untitled) (Journal of the College of Basic Education, 2023)
The study aimed to prepare a training curriculum using hypoxia method using a mask(Hypoxik) in accordance with the abilities of young players in handball and to identify its impact onDeveloping some special physical abilities of young handball players; The two researchers usedThe experimental method designed by the experimental and control group with pre and post test ©On a sample of young players in the First Division Clubs League in Baghdad (for my clubAl-Jaish and Al-Karkh) for the sports season (2013-2014) and the capabilities of the distinctive force were determinedWith the speed of the arms and legs, the transitional speed, the endurance of speed, and the preparation of a curriculumMy training using the hypoxic method using a hypoxic mask was applied to the groupExperimental (32) training units that were carried out during (8) weeks, at (4) training units, for a period ofTwo months, and the results were processed after the post-tests, and the most important of them was that the training curriculum had a styleLack of oxygen by using the (hypoxic) mask has a positive effect on developing the characteristic strengthWith the speed of the arms and legs of the young handball players who trained with him; and outperform themdeveloping players who trained without him; And that the training curriculum method hypoxiaUsing a hypoxic mask helped to improve the transitional speed and endurance of the two legsyoung handball players who trained with it; And their superiority improves them in the players whoPractice without it.